Curriculum design competence in initial level: successes and failures - Giacosa, Andrea (2016)
The document generates an outline of the perspective of curriculum and adjustments made from the public to the private level to be considered as a curriculum design skills. Concluding predisposition which should include education to train students in the skills , attitudes and thus complement from their life experiences.